An Examination of Primary School Mathematics Pre-Service Teachers’ Scores in Calculus-I Course According to the Updated Curriculum: The Case of Derivative Concept - Koyuncu, Mahmut Sami; Saygı, Elif; Erol, Ramazan (My University, 2022)
This study aims to examine the change in pre-service teachers’ Calculus-I course passing scores in the undergraduate curriculum of primary school mathematics teaching program through comparing the previous curriculum and the new curriculum updated in 2018. This study is a causal comparison study, as it aims to compare the existing differences. The study group of the research consists of 212 pre-service teachers in primary school mathematics education department at a state university in the Aegean region, Turkey. The data within the scope of the research were obtained from the Calculus-I course midterm and final exams of the pre-service teachers in the previous curriculum (2016-2017 fall and 2017-2018 fall) and in the updated curriculum (2018-2019 fall and 2019-2020 fall). The courses were taught by a single instructor in all semesters, and an interview was conducted with the responsible instructor about the course. In the study, when the effect of the university placement score was held constant, whether the Calculus-I course passing scores differed according to the previous and updated curricula was examined by nonparametric covariance analysis. The study revealed that the average of the university placement scores of the pre-service teachers in the previous and updated curricula was very close to each other, but the average scores of passing the Calculus-I course were statistically higher in the previous curriculum than in the updated one. The main reason for this is thought to be the reduction of the Calculus-I course hours in the new curriculum.